Comparison of the influence of acoustically enhanced pulsating water jet on selected surface integrity characteristics of CW004A copper and CW614N brass. (November 2017) - Lehocká, D.; Klichová, D.; Foldyna, J.; Hloch, S.; Hvizdoš, P.; Fides, M.; Botko, F.
Graphical abstract: Abstract: Acoustically excited pulsating water jet cutting (PWJ) is technological modification of material disintegration. From the reason of not detail described area of area of acoustically excited pulsating water jet with using circular nozzle is article focused on further research of mentioned technology. Presented article is focused on evaluation of surface integrity of copper CW004A and brass CW614N, changes in surface layer and strengthening in subsurface layer after impact of acoustically excited pulsating water jet. Surface topography was evaluated by using optical profilometry. Changes in surface layer were evaluated based on mass material removal Δ m [mg/s] and maximal depth of penetration PWJ hmax [mm]. Strengthening in subsurface layer was monitored by nanoindentation measurement with Berkovich indenter. Evaluation of subsurface layers discover slight strengthening under disintegrated surface with lower elasticity.